Clinical profile of dengue encephalopathy: A series of twelve cases and a profile of other complications - Biswajit Bhuyan; Bandita Panda; Rabinarayan Rout; Lalatendu Mohanty; Bangam Rajendra Prasad Rao (Journal of Family Medicine and Primary Care)
Dengue fever is a mosquito borne viral infection caused by a Flavivirus with four serotypes named DENV 1 to 4, is becoming a significant public health hazard. The spectrum of dengue presentation varis from asymptomatic to severe dengue. Neurological manifestation in dengue fever is an unusual presentation, however metabolic encephalopathy/vascular strokes, resulting with organ dysfunction occurs in severe dengue infection. We report a case series of 12 dengue patients having encephalopathy from Odisha, Bhubaneswar from a total of 2065 diagnosed dengue positive patients during May 2019 to Jan 2024. Clinically dengue encephalopathy patients diagnosed from altered sensorium with metabolic and radiological parameters. In addition, complications of dengue fever had been compiled. We present these 12 cases having dengue encephalopathy with varied complication and managed with immediate clinical interventions to prevent negative outcomes and to improve the quality of life through early detection. Mortality was one out of 12 cases.